PROFITABILITY ANALYSIS OF BORO RICE FARMING: THE CASE OF NAOGAON DISTRICT OF BANGLADESH - Md Asduzzaman Kiron; Md Khairul Islam (Agricultural Socio-Economics Journal, 2023)
Agriculture is one of the major sectors in Bangladeshâ€™s economy because of its contribution to gross domestic product and employment. This study investigates farm profitability in Boro rice cultivation in the Naogaon district of Bangladesh. Using simple random sampling, 45 farmers were selected randomly from 4 villages in Naogaon District.Â  Participants went through structured interviews, and the responses were recorded. Descriptive statistics, cost-benefit analysis, and Cobb-Douglas production function were used to analyze this study. Ordinary least square was used as the regression technique. Empirical results obtained from production function analysis considering hired labor, pesticides, planting, harvest & transport, and machinery costs positively affect Boro rice production while seed, fertilizer, plowing, and irrigation cost negatively affect Boro rice production. Boro rice cultivation was found profitable in the study area. The average per bigha net return of Boro farming was Tk. 1694.11. The study also discovered some challenges in Boro rice cultivation in that particular area. In the end, the study suggests some policies to enhance profitability in Boro rice cultivation in the Naogaon district and overcome the challenges. This study would be useful for the agricultural economics researchers and the policymakers of Bangladesh and countries with similar economies.